Comparative Analysis of Interbody Cages Versus Tricortical Graft with Anterior Plate Fixation for Anterior Cervical Discectomy and Fusion in Degenerative Cervical Disc Disease - Singh, Pritish (J Clin Diagn Res, 2016)
INTRODUCTION: Multiple techniques and modalities of fixation are used in Anterior Cervical Discectomy and interbody Fusion (ACDF), each with some merit and demerit against others. Such pool of techniques reflects lack of a consensus method conducive to uniformly good results. AIM: A prospective study was done to analyse safety and efficacy of tricortical autograft and anterior cervical plate (Group A) with cylindrical titanium cage filled with cancellous bone (Group B) in procedure of ACDF for single level degenerative cervical disc disease. MATERIALS AND METHODS: Twenty patients with degenerative cervical disc disease were included in study for ACDF. After a computer generated randomisation, ten patients (10 segments) were operated with anterior locking plating and tricortical iliac crest graft (Group A, Tricortical graft group), while ten patients(10 segments) were operated with standalone cylindrical titanium cages filled with cancellous bone harvested using minimally invasive methods (Group B, Cage group) from April 2012 to May 2015. Odoms’s criteria, visual pain analogue score and sequential plain radiographs were obtained to assess for clinic-radiological outcome. RESULTS: According to Odom’s system of functional assessment, 9 patients from each group (90%) experienced good to excellent functional recovery and 9 of 10 (90%) patients of each groups were satisfied with outcome. In both groups, relief in neck pain or arm pain was similar without any statistical difference as assessed by visual analogue score. Fusion was present in 10 of 10 (100%) patients in tricortical graft group and 10 of 10 (100%) in cage group at the end of 6 months. There was no implant related complications in cage group. Transient postoperative dysphagia was recorded in 3 patients (2 in Group A and 1 in group B), which resolved within 3 days. In tricortical graft group, graft collapse and partial extrusion was detected in one patient, which did not correspond with good results obtained in particular patient. CONCLUSION: Use of cylindrical titanium cage packed with cancellous bone graft provide adequate stability and reliable functional outcome after fusion in cervical disc disease. Titanium cages for fusion after cervical discectomy constitute a safe and equally efficient alternative to tricortical autograft with anterior cervical plate by providing adequate stability and cessation of rediculopathy symptoms.